2021
DOI: 10.17159/2413-3051/2021/v32i2a5856
|View full text |Cite
|
Sign up to set email alerts
|

The South African informal sector’s socio-economic exclusion from basic service provisions: A critique of Buffalo City Metropolitan Municipality’s approach to the informal sector

Abstract: This study explores the exclusion of informal micro-enterprises from the provision of basic urban infrastructure services in Duncan Village in East London, South Africa. It focuses on the informal food sector, which is dominated by women who are often held back from participating in economic activities that are more productive, as well as from social and political functions. Basic urban infrastructures, such as trading shelters with water and electricity connections provided by municipalities, are often expens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In the continuous monitoring and additional services provision: The current study showed that there is an impact on the usage of dirty cooking fuels and the health of vendors. Masuku and Nzewi (2021) stated that we keep in mind that informal food enterprises occasionally use traditional sources of energy, such as wood and charcoal, not because they lack access to electricity, but rather because of the type of product they are preparing [ 30 ]. The lack of access to modern and efficient energy sources has a negative impact on the user’s health, and using wood and charcoal can cause respiratory diseases, moreover, there is a safety aspect of the usage of an open fire, as various markets have burnt over the years, hence the need for the monitoring and empowerment of vendors.…”
Section: Resultsmentioning
confidence: 99%
“…In the continuous monitoring and additional services provision: The current study showed that there is an impact on the usage of dirty cooking fuels and the health of vendors. Masuku and Nzewi (2021) stated that we keep in mind that informal food enterprises occasionally use traditional sources of energy, such as wood and charcoal, not because they lack access to electricity, but rather because of the type of product they are preparing [ 30 ]. The lack of access to modern and efficient energy sources has a negative impact on the user’s health, and using wood and charcoal can cause respiratory diseases, moreover, there is a safety aspect of the usage of an open fire, as various markets have burnt over the years, hence the need for the monitoring and empowerment of vendors.…”
Section: Resultsmentioning
confidence: 99%
“…In South Africa, the informal economy, which currently includes Uber DLP, also has a significant share of total employment, with over 2.5 million people making up 20% of total employment in the country, providing a means of subsistence and income for millions of workers and business owners, and contributing about 5.1% of gross domestic product (GDP) (Masuku & Nzewi, 2021). As we have seen, Uber driving is treated as informal in South Africa because it is not yet covered by labour regulations and the drivers are classified as independent contractors.…”
Section: The Case Of Uber Dlp In South Africamentioning
confidence: 99%
“…Despite their important role in food systems, especially for the food and nutrition security and livelihoods of lower-income individuals, informal businesses face many challenges. According to literature, these can be very diverse -including exclusion from basic service provisions, such as trading shelters with water and electricity connections (Masuku and Nzewi, 2021) and access to formal sources of business finance; competition from formal businesses in access to public services and infrastructure (Battersby et al, 2016); lack of access to education and training, resulting in financial illiteracy, vulnerability to bribe and excessive taxation; and lack of government support in times of covariate shocks, such as the COVID-19 pandemic and Ebola (Battersby, 2020;Guven et al, 2021;Rukasha et al, 2021).…”
Section: Limitations and Main Challengesmentioning
confidence: 99%